Clinical responses of vaccinated Bali cattle against challenge with a field isolate of Bovine Herpesvirus- 1 - Sudarisman . (Indonesian Center for Animal Research and Development (ICARD), 2001)
The aim of this study is to investigate the post challenge clinical responses of Bali cattle vaccinated with an inactivated vaccine of a field isolate Bovine Herpesvirus-1 after being challenged with the same virus. Twenty eight Bali cattle were divided into two groups of ten animals, one of which was vaccinated with a single dose and the other one was vaccinated with a booster dose of vaccination, and the rest of the animals were remained untreated as a control group. One month after the last vaccination, a half number of animals in each group were challenged intravenously with 5 x 108 TCID 50 pathogenic strain of BHV-1 local isolate. Clinical signs were observed from day 0 to day 14 after challenge. These observed included body temperature, mucosal membrane changes of nostril, vagina and palpebrae, hyperlacrimation and hypersecretion of nose and eyes. General clinical changes and mucous membrane lesions of nostril were scored from 0 to 3. The results showed that the non-vaccinated animals: elevated temperature (up to 40.1°C), hyperlacrimation, nasal discharge and mucosal hyperaemia of nostril and vagina after challenge. The duration of illness ranged from 3 to 7 days. Symptoms appeared after an incubation periode of 3 days and disappeared after 5 days (day 9). These clinical symptoms didn’t appear on the vaccinated animals with single or boostered vaccination. One month after vaccination, the antibody titre reached 211 (2048) based on serum neutralisation test (SNT). These vaccinated animals showed good immune respons to BHV-1. Key words: Clinical responses, inactivated vaccine, field isolate, BHV-1, Bali cattle